2002
DOI: 10.3171/spi.2002.97.2.0235
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary plasma cell granuloma in the cervicothoracic spine

Abstract: ✓ Intraspinal plasma cell granuloma, which is a nonneoplastic entity, is extremely rare. To date, only four cases have been documented in the spinal meninges. The authors report the first case of a C7—T1 intramedullary plasma cell granuloma. After excision of the lesion, the patient's gait and bladder dysfunction improved. This plasma cell granuloma initially showed no delineated mass on T1-weighted magnetic resonance (MR) images, low signal intensity on T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
14
2
Order By: Relevance
“…In contrast, IPTs show hypointensity on T2W images (Han and others 1996, Aizawa and others 2002, Despeyroux-Ewers and others 2003, Loderstedt and others 2010), which differ from the signal intensity in our case. However, the signal intensity on the T2W images is thought to be variable within the IPT (Seol and others 2005).…”
Section: Discussioncontrasting
confidence: 84%
“…In contrast, IPTs show hypointensity on T2W images (Han and others 1996, Aizawa and others 2002, Despeyroux-Ewers and others 2003, Loderstedt and others 2010), which differ from the signal intensity in our case. However, the signal intensity on the T2W images is thought to be variable within the IPT (Seol and others 2005).…”
Section: Discussioncontrasting
confidence: 84%
“…There are conflicting reports concerning signal intensity changes of IMT on T2-weighted image. A few articles have reported that IMT usually has low signal intensity on T2-weighted images with homogeneous or heterogeneous enhancement (5,7,8,10,13). Han et al (7) suggested that T2 hypointensity of an IMT might be explained by a relative lack of both free water and mobile protons within a fi- brotic lesion; whereas, there are also a few reported cases of IMT demonstrating hyperintensity on T2-weighted images (9,14).…”
Section: Discussionmentioning
confidence: 99%
“…IMT has a propensity to mimic clinically and radiologically a malignant tumor (2,3). There are no distinguishable characteristic findings of IMT, and various signal intensity of the mass was reported at one time point (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). We report a rare case of pathologic-proven spinal epidural IMT which showed not only changing signal intensity on magnetic resonance imaging (MRI), but also corresponding change on computed tomography (CT) and bone scan, without any treatment over a 2-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, since the first description by Eimoto et al [5], only nine cases of intradural extramedullary [3][4][5][6][7][8][9][10][11] tumors have been reported in the literature (Table 1). A few other cases of epidural [14][15][16][17] or intramedullary [18][19][20] spinal IMT have been reported. According to the previous cases reported, the time to diagnosis of intradural extramedullary spinal IMT ranges from 2 to 48 months.…”
Section: Discussionmentioning
confidence: 99%